Depression and violence in adolescence and young adults: Findings From three longitudinal cohorts - Yu, R; Aaltonen, M; Branje, S; Ristikari, T; Meeus, W; Salmela-Aro, K; Goodwin, G; Fazel, S (Elsevier, 2017)
Objective Despite recent research demonstrating associations between violence and depression in adults, links in adolescents are uncertain. This study aims to assess the longitudinal associations between young people’s depression and later violent outcomes. Method We used data from three cohorts with different measurements of depression exposures and subsequent violent outcomes. In a Dutch community cohort Research on Adolescent Development And Relationships (RADAR; N = 623) and a population-based British birth cohort Avon Longitudinal Study of Parents and Children (ALSPAC; N = 4,030), we examined the longitudinal links between adolescent depressive symptoms and violent behaviors from age 13 to 17 years. In a total Finnish birth cohort (FBC 1987; N = 57,526), we estimated risk of violent convictions in individuals clinically diagnosed with depression from age 15-27 years. Results During a mean follow-up period of four years, the adjusted odds ratio (aOR) of violent behaviors per unit of increase in depressive symptoms was 1.7 (95% CI: 1.2-2.5) in the Dutch RADAR community sample and 1.8 (95% CI: 1.4-2.3) in the British ALSPAC birth cohort. In the FBC 1987 cohort, the aOR of violent convictions was 2.1 (95% CI: 1.7- 2.7) among individuals with a depression diagnosis compared with general population controls without depression. All risk estimates were adjusted for family socioeconomic status and previous violence. Conclusion Consistent findings across three longitudinal studies suggest that clinical guidelines should consider recommending risk assessment for violence in young people with depression. The benefits of targeting risk management in subgroups by gender need further investigation.